Loss of CD44dim Expression from Early Progenitor Cells Marks T-Cell Lineage Commitment in the Human Thymus - Canté-Barrett, Kirsten; Mendes, Rui D.; Li, Yunlei; Vroegindeweij, Eric; Pike-Overzet, Karin; Wabeke, Tamara; Langerak, Anton W.; Pieters, Rob; Staal, Frank J. T.; Meijerink, Jules P. P. (Frontiers in Immunology, 2017)
Human T-cell development is less well studied than its murine counterpart due to the lack of genetic tools and the difficulty of obtaining cells and tissues. Here we report the transcriptional landscape of 11 immature, consecutive human T-cell developmental stages. The changes in gene expression of cultured stem cells on OP9-DL1 match those of ex vivo isolated murine and human thymocytes. These analyses led us to define evolutionary conserved gene signatures that represent pre- and post- αβ T-cell commitment stages. We found that loss of dim expression of CD44 marks human T-cell commitment in early CD7+CD5+CD45dim cells, before the acquisition of CD1a surface expression. The CD44-CD1a- post-committed thymocytes have initiated in frame TCR rearrangements that is accompanied by loss of capacity to differentiate towards myeloid, B- and NK-lineages, unlike uncommitted CD44dimCD1a- thymocytes. Therefore, loss of CD44 represents a previously unrecognized human thymocyte stage that defines the earliest committed T-cell population in the thymus.